The ASADAS: A Legal-Practical Analysis of its Nature and its Responsibilities. - Cuadrado Quesada, Gabriela (2021)
This article analyzes the figure of the Administrative Associations of Communal Aqueducts and Sewers (ASADAs) in Costa Rica from a legal-practical perspective. It discusses the birth and evolution of ASADAs in the legal system and investigates how they were created empirically and how they have evolved in practice. The article reflects on the importance of redefining the ASADAs from a legal perspective, considering their origins and their communal nature. Likewise, it discusses and problematizes the current challenges of these figures, particularly their new role as regulators of land use planning.